Design Issues of Wireless Sensor Network and Open Research Challenges - K. Nighot, Mininath (EAI Endorsed Transactions on Energy Web, 2020)
WSN is becoming more popular day by day among researchers due to its vast real-time applications. Various design parameters directly affect the overall performance and lifetime of the network. The design of WSN system is depends upon application. Many parameters need to consider to design WSN system such as number of nodes, types of nodes, routing strategies, way of communication among the nodes and in the network, etc. The network structure and its operations categorize the WSN into flat-based and cluster-based systems. At present, the major challenge is designing and deploying the WSN system. The objective of the paper is to study and analyze all the essential parameters to overcome the challenge. The paper also critically reviews the literature. Finally, the paper is summarized and concluded with open research issues to design robust, low cost, energy-aware WSN systems.
Keywords: WSN; Flat based WSN; Cluster-based WSN; Design Issues; Open issues